SACRIFICE FOR LOVE IN JOHN COLLIER’S THE CHASER AND JESSE STUART’S LOVE - Abu Fanani (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2014)
In this article, the researcher analyzes and compares sacrifice for love in John Collier’s the Chaser and Jesse Stuart’s Love. The researcher then uses formalism theory in that the researcher analyzes and compares the characters’ sacrifice for love within the short stories themselves regardless the condition, place, and time when the authors wrote the short stories. At last, the researcher draws conclusion that in the similarities both short stories have similar theme, namely, love needs sacrifice. Both characters sacrifice a valuable thing, instead. Whilst, as to the differences, in John Collier’s the Chaser, the character sacrifices his pride and love for little money, in Jesse Stuart’s Love, sacrifices the life.